Neutrophil association and degradation of human C-reactive protein [Microfiche] - Beer, S. M.(Sussanna Maria) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Med. Sci.) -- University of Stellenbosch, 1988.